Estimación de la Aptitud Combinatoria General y Específica de líneas F1 de arroz (Oryza sativa L...ssp.indica) - Montoya Muñoz, Milton Ernesto (2019)
The present experimental work designated “Estimation of the General and Specific Combinatorial Aptitude of F1 rice lines (Oryza sativa L ... ssp.indica). It was executed in the Experimental Farm "El Palmar" Belonging to the Faculty of Agricultural Sciences (U.T.B), CEDEGE Project, and province of Los Ríos, located in KM 12 of the Babahoyo –Montalvo road. The main objectives were: To determine the effects of the General Combinatorial Fitness (ACG) and Specific Combinatorial Fitness (ACE) of 15 F1 lines of rice (Oryza sativa L.ssp.indica) confronted with their parents; Identify crosses of high agronomic potential; Evaluate the agronomic and production characteristics of F1 rice populations. During the investigation, the following variables were evaluated: Plant height (cm), vegetative vigor, days to flowering (days), vegetative cycle (days), flag leaf length (cm), flag leaf width (cm ), number of tillers per plant, number of panicles per plant, panicle length (cm), shelling (%), number of grains per panicle, sterility (%), weight of one thousand grains (g), grain yield per plant (g), length (mm), width (mm) and husked grain shape. The results of these variables were submitted to the statistical analysis which was used the Randomized Complete Blocks Design (DBCA), using an analysis of variance (ANAVA) with 21 treatments and 4 repetitions, the ACG General Combinatorial Aptitude was also determined. ) and the Specific Combinatorial Fitness (ACE), using Griffing method II. According to the results obtained, the F1 lines of Indica-type rice showed an intermediate height, and are considered according to the analysis of vegetative vigor as very vigorous plants, the progeny of the BR-101 / FL-110 crossing proved to be a segragant desirable since it stood out for a good yield of grain per plant of 85.98 g, also reaching the highest average number of tillers and panicles per plant with values of 21 and 19 respectively. The line that obtained higher values for flag sheet width and for the panicle length variable corresponds to the crossing: FI-106 / G-112. The F1 progeny belonging to the SH-108 / G-112 cross was the one that showed the highest value in the variable number of grains per panicle with an average of 168 grains and presented the highest average of flag leaf length with 44.48 cm. Through these results obtained from the investigation, it is concluded that the selection processes of the best progenies must be continued for both agronomic and production characteristics, in order to achieve a variety that is of desirable characteristics and serves as a planting alternative to the rice sector